Sexual dysfunction and its determinants in Malaysian women with rheumatoid arthritis - Shahar, Mohammad Arif; Hussein, Heselyn; Sidi, Hatta; Shah, Shamsul Azhar; Mohamed Said, Mohd Shahrir (Wiley-Blackwell Publishing Asia, 2012)
AIM: To determine the prevalence of sexual dysfunction (FSD) among women with rheumatoid arthritis attending the Rheumatology Clinic in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) and Hospital Putrajaya, Malaysia, and to determine its associations with potential clinical and disease activity factors. METHOD : This was a cross-sectional study involving women with rheumatoid arthritis between the ages of 20 and 60 years. A validated Malay Version Female Sexual Function Index (MVFSFI) was administered to diagnose FSD. Sociodemographic and disease activity profiles were obtained and those who had and did not have FSD were compared. RESULTS: Among 63 respondents, 51 patients were included in the analysis for FSD. The prevalence of FSD in women with rheumatoid arthritis attending UKMMC and Hospital Putrajaya Rheumatology Clinic was 29.4%. Erythrocyte sedimentation rate (ESR) and Disease Activity Score in 28 joints (DAS28-ESR) correlates with MVFSFI score with r = −0.364 (P = 0.009) and r = −0.268 (P = 0.057), respectively. Sociodemographic factors that correlate with MVFSFI score were: patient's age (r = 0.520, P < 0.001); duration of marriage (r = −0.355, P = 0.001); husband's age (r = −0.460, P = 0.001); age of oldest child (r = −0.449, P = 0.001); and age of youngest child (r = −0.627, P < 0.001). CONCLUSION : We found in this study that the prevalence of FSD in rheumatoid arthritis in our centers was 29.4%. Age and family dynamics appear to be more important predictors compared to disease activity.